Stress Dependency of Creep Response for Glass/Epoxy Composite at Nonlinear and Linear Viscoelastic Behavior - N. Nosrati; A. Zabett; S. Sahebian (International Journal of Polymer Science)
This research is aimed at comparing the stress dependency of creep viscoelastic behavior for glass/epoxy composite and neat epoxy close to the glass transition temperature and room temperature. Long-term creep performance of quasi-unidirectional composites and quasi-isotropic stacking sequence composites is modeled based on the time-stress superposition principle (TSSP). Linearity and nonlinearity of viscoelastic behavior and stress-dependence correlations were investigated for quasi-isotropic stacking sequence composite at 25°C and 50°C (near the glass transition temperature). Stress dependency of creep stages (primary, secondary, and tertiary) of neat epoxy was evaluated at this range of temperature. The prediction results of composite at room temperature show that the raising of the stress levels leads to the acceleration of viscoelastic strain values, but the creep compliance does not present any dependency. Besides, the reduction of viscoelastic ability is realized by measuring less amount of creep compliance at higher stress level in the glass transition temperature. These observations confirmed the linearity and nonlinearity of viscoelastic behavior at room and glass transition temperature, respectively. Similar results of neat epoxy revealed that the increase in the stress level accelerates the strain values at room temperature and decreases the creep resistance at glass transition temperature. Failure morphologies of epoxy sample fractured at room temperature are included scarp, cusp, and river line; however, close to the glass transition temperature, more expansive mirror zones appeared. Fiber architecture significantly affected the secondary stage regime by providing load-bearing ability. Thereby, creep rate reduction and enhancement of creep lifetime and creep resistance would be reported using unidirectional reinforcing in contrast to those of the multilayer sequence one.